Indigenous governance clans, constitutions, and consent - Wilkins, David E. 1954- (Oxford University Press, 2024)
"After decades of federal dominance and dependence, Native governments now command attention as they exercise greater degrees of political, economic, and cultural power. Given the weight and importance of many issues confronting Native peoples today, these governments arguably matter even more to their peoples and to the broader society than ever before. Native governments have become critically important as the chief providers of basic services and the authors to solutions to collective problems in their societies. As major actors within the realm of democratic politics, they increasingly wield their powers to educate and advocate regarding Indigenous concerns. For many communities (including non-Native neighbors) they are the largest spenders and employers. They have also become adept at negotiating intergovernmental agreements that protect their peoples and resources while strengthening their unique political status. Native peoples and governments are also navigating the devastating and lingering health and economic impact of COVID-19; the profound environmental problems that have been exacerbated by climate change; and jurisdictional conflicts with local, state, and federal actors. Indigenous Governance is a comprehensive, critical examination of Native poltical systems: the senior political sovereigns on the North American continent in terms of their origin, development, structures, and operation. Author David E. Wilkins provides the recognition and respect due to Indigenous governments, while offering a considered crituique of their shortcomings as imperfect, sovereign institutions. This appraisal will highlight their history, evolution, internal and intergovernmental issues, and diverse structures." -- Back cover
Includes bibliographical references (pages 437-448) and index
Keywords: Geschichte; Indigenes Volk; Indianer; Politische Beteiligung; Repräsentation -- Politik; USA; Tribal government / United States; Indians of North America / Politics and government; Indigenous peoples / Government relations